DETERMINAN PENGAMBILAN KEPUTUSAN KONSUMEN DAGING AYAM RAS DI PASAR TRADISIONAL MURNI DAN SNI KABUPATEN SITUBONDO - Rara Winda Apriliana Dzakiyyah; Titin Agustina (University of Jember, 2021)
Consumer decision making to buy purebred chicken meat in pure traditional markets is higher than SNI traditional markets which have advantages in cleanliness, facilities, and service. This study aimed to determine the characteristics of consumers and the determinants of consumer decision-making to buy chicken meat in pure and traditional SNI markets. The research method used was descriptive-analytic. The sample was 100 people with convenience sampling. Chi-square and Mann-Whitney tests were used to analyze consumer characteristics, and logistic regression to analyze consumer decision-making factors. The results showed that there was a relationship between the consumer's occupation and the decision to buy chicken meat, and there were differences in education and income between consumers in pure traditional markets and SNI traditional markets. Variables that significantly influence consumer decisions are the price of purebred chicken, location, number of family members, and education. For managers of traditional markets in Situbondo Regency, it is necessary to arrange shops, improve market facilities such as waiting rooms and maintain cleanliness so that they remain consumer choices.